Practice Pointer: Assessment of child or young person with a possible eating disorder - Bould, H; Newbegin, C; Fazel, M; Stewart, A; Stein, A (BMJ Publishing Group, 2017)
Assessing young people with possible eating disorders can be complex for a variety of reasons, including managing confidentiality and risk (for example, a young person not wanting their parent to be involved, or a parent presenting with concerns about their child), the young person or parent not being aware of the severity of the illness, and difficulty in knowing how questions can be sensitively phrased. This Practice Pointer will offer advice on building therapeutic relationships in consultation with a child or young person, and with their parent(s), what information to gather and how to do so sensitively, and how to discuss the role of the parent or carer in treatment. We recommend that it is read alongside the accompanying Clinical Update for detailed notes on examination, investigations, when to refer, and risk. The advice is based on expert experience. We use the female pronoun throughout as eating disorders are more prevalent in females, but it should be noted that they can and do also occur in males.